2010
DOI: 10.1088/0953-4075/43/23/235202
|View full text |Cite
|
Sign up to set email alerts
|

Double photoionization of atoms and ions confined in charged fullerenes

Abstract: The double photoionization of a helium atom and a singly charged lithium positive ion enclosed in charged Cq60 fullerenes is studied using the time-dependent close-coupling method. Continuum raising and lowering effects are seen in the shift of the double-ionization threshold of the confined atom or ion. Confinement resonances in the double-photoionization cross section, previously observed for helium confined inside a neutral fullerene, persist for helium confined in both positively and negatively charged ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
1
23
1
Order By: Relevance
“…However, at lower energies, there is still a large deviation from the isolated He results for α = 0.2. Unlike the damping effect illustrated in [8], where the amplitude of the confinement oscillations decreased as the confining potential was made shallower and wider, here there is no phase shift in the locations of the peaks of the confinement resonances, showing that this is a distinct effect.…”
Section: Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…However, at lower energies, there is still a large deviation from the isolated He results for α = 0.2. Unlike the damping effect illustrated in [8], where the amplitude of the confinement oscillations decreased as the confining potential was made shallower and wider, here there is no phase shift in the locations of the peaks of the confinement resonances, showing that this is a distinct effect.…”
Section: Resultscontrasting
confidence: 60%
“…width in the experiment of Kilcoyne et al [2]. The sensitivity to the depth and width of the confining potential was investigated for double photoionization in [8]. It was found that as the confining potential becomes wider and shallower (while maintaining the same electron affinity), the confinement resonances are decreased in amplitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We use here the description of the problem [45] (see eqs. [15][16][17][18] for the case of the ks-state of the spherically symmetric one-electron system with the exact stationary wave-function Ψ = Ψ ks . In the presence of the external electric field with constant strength F and the potential −Fz one can use for the first-order correction to the wave function as an approximation by linear combination of M functions of the form f j Ψ ( j = 1/M)…”
Section: Orcidmentioning
confidence: 99%
“…A number of phenomenological potentials have been used to model atoms within cavities [3], atoms under pressure [4], impurities in quantum dots or nano crystals [5], nanopores [6,7], fullerenes [8] and foreign atoms in liquid helium environment [9] etc. The study of quantum dots (QD) has got considerable attention in recent times due to its fundamental importance in theoretical researches as well as in fabricating new functional devices.…”
Section: Introductionmentioning
confidence: 99%